2011
DOI: 10.1007/978-3-642-24500-8_44
|View full text |Cite
|
Sign up to set email alerts
|

Bringing Empathy into Play: On the Effects of Empathy in Violent and Nonviolent Video Games

Abstract: Abstract. While violent media has adverse effects on cognition, emotion and behavior, prosocial content promotes these variables in a prosocial way. Greater individual levels of empathy as well as increasing the level of empathy in media content typically foster prosocial behavior and reduce aggression. Two experiments replicated game content findings, and also showed that inducing empathy prior to a video game had a positive influence on behavior. However, under certain circumstances, inducing empathy before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Participants in the study of Fischer et al (2012) were likelier to steal pens or candy bars from the laboratory after playing a delinquency-reinforcing game compared to a delinquencyneutral game. Using a similar procedure, this finding was replicated by Happ, Melzer, and Steffgen (2011), who also observed that playing a violent game leads to less prosocial behavior, which was assessed by the willingness to fill out an optional questionnaire. Greitemeyer and McLatchie (2011) showed that another participant's (a confederate) job-relevant qualifications were evaluated less positively after playing a violent game.…”
Section: Aggressive Behaviormentioning
confidence: 72%
“…Participants in the study of Fischer et al (2012) were likelier to steal pens or candy bars from the laboratory after playing a delinquency-reinforcing game compared to a delinquencyneutral game. Using a similar procedure, this finding was replicated by Happ, Melzer, and Steffgen (2011), who also observed that playing a violent game leads to less prosocial behavior, which was assessed by the willingness to fill out an optional questionnaire. Greitemeyer and McLatchie (2011) showed that another participant's (a confederate) job-relevant qualifications were evaluated less positively after playing a violent game.…”
Section: Aggressive Behaviormentioning
confidence: 72%
“…2 In addition to the game content itself, however, identification with violent characters increases aggression for both watching TV 3 and playing video games. [4][5][6] The inherent characteristics of video games further support identification. Players may adopt novel identities, ''try on'' ideal characteristics, 7 share game characters' goals, and experience their feelings, which may further intensify the perceived joy of playing the game.…”
Section: Introductionmentioning
confidence: 99%
“…9 As violence makes video games especially appealing 10 and with media frequently presenting violent ''heroes'', 11 the role of identification with a violent video game character 4 or feeling empathy for a violent character 12 are important aspects in explaining negative video game effects. So far, few studies have directly compared the effects of video game characters 5,12 that differ with regard to users' perception of their morality (good vs. evil). 5,13,14 The present study was designed to close this empirical gap.…”
Section: Introductionmentioning
confidence: 99%
“…The perception of the concept of empathy varies from an emotional response to others' feelings to the cognitive ability to understand these feelings. In addition to these two often -used major components of cognitive and affective empathy, a dimension for empathy in fictional contexts broadens the concept [5].…”
Section: Introductionmentioning
confidence: 99%